An Acute Anterior Reinfarction Complicating with Transient Symptomatic Total Atrioventricular Block - Hendiperdana, Mochamad Rizky; Firdaus, Isman (The Indonesian Heart Association, 2025)
In “An Acute Anterior Reinfarction Complicating with Transient Symptomatic Total Atrioventricular Block” (Indonesian Journal of Cardiology, 43(3), 130-6. https://doi.org/10.30701/ijc.1216), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1216. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. In the original published version of this article, there is an error in the author’s name. The author’s name has been changed to “Mochamad Rizky Hendiperdana” from the previous “Rizky Hendiperdana.”The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1216